Irrelevance of USF2 rs916145 polymorphism with the risk of biliary atresia susceptibility in Southern Chinese children. Issue 2 (28th February 2020) - Chen, Lei; Fu, Ming; Tan, Ledong; Zhao, Jinglu; Xu, Xiaogang; Lin, Yuzhen; Zhong, Qian; Zhong, Ruisui; Zhang, RuiZhong; Zeng, Jixiao
Abstract: Backgrounds: Biliary atresia (BA) is a very rare neonatal disease, however, it has been the most common cause of obstructive jaundice in infancy. The complex pathogenesis of BA is not entirely clear and a lot of possible pathogenic mechanisms have been proposed to explain the etiology of BA, including genetic, inflammatory, environmental and developmental abnormalities. As a transcription factor, USF2 gene rs916145 polymorphism has been shown to be related to the risk of BA. Methods: We examined the USF2 rs916145 genotype in a large case–control study consisting of 506 BA patients and 1473 healthy controls, using the MassARRAY iPLEX Gold system (Sequenom). Odds ratios (ORs) and 95% confidence intervals (CIs) were used to evaluate the association between the USF2 gene rs916145 polymorphism and BA susceptibility. Results: The frequency of different genotypes showed no statistical significance (GG/GC, OR: 1.09, P =0.470, 95% CI: 0.87–1.35; GG/CC, OR: 0.86, P =0.378, 95% CI: 0.62–1.20). No obvious association was revealed between the USF2 gene rs916145 polymorphism and BA susceptibility. Conclusion: USF2 rs916145 polymorphism may not be the best predictor of BA.